Growth Rate Analysis of an Untreated Glomus Vagale on MRI - Jeffrey Tzu-Yu Wang; Allen Yu-Yu Wang; Sheila Cheng; Lavier Gomes; Melville Da Cruz (Case Reports in Otolaryngology)
Paragangliomas are slow growing, hypervascular neuroendocrine tumors that develop in the extra-adrenal paraganglion tissues. Paraganglioma involving the vagus nerve ganglia is termed glomus vagale. The slow growth of head and neck paragangliomas especially in the absence of symptom may obviate the necessity for any active intervention, in which case, a “wait and scan” policy is implemented involving long-term clinical and radiologic follow-ups. We present a case of a 71-year-old female with an untreated left glomus vagale who underwent a conservative “wait and rescan” plan of management and the tumor was observed with 8 serial MRI scans over a period of 7.4 years. A growth rate analysis was conducted which demonstrated a slow growth. A literature review of radiologic studies examining the natural history of head and neck paragangliomas was also performed.